Network Security Issues and Tools for Testing Security in Computer Network. - ShwetanakSaurabh, Neeraj Kumar, Rachit Gupta, (International Journal of Scientific Research and Management (IJSRM), 2017)
This research paper tries to put forward a solution for improving the security of network. This study mainly focuses on information security standards, based on the ISO 27000 series. Further, the thesis implements the suggested solution inside a simulated network and monitors and evaluates it by using the network vulnerability scanner.With regard to the suggested solution, it is necessary to discuss the concepts of information security standards, and different security models and observe the advantages and limitations of them. Therefore, this research includes the definition of information security standards and the advantages and limitations of security models.